PENGARUH HALAL SUPPLY CHAIN DAN INOVASI PRODUK TERHADAP KINERJA UMKM MAKANAN DAN MINUMAN DI KOTA PEKANBARU: THE EFFECT OF HALAL SUPPLY CHAIN AND PRODUCT INNOVATION ON THE PERFORMANCE OF FOOD AND BEVERAGE MSMES - Samsiar, Samsiar; Nurmayanti, Poppy; Khoiriyah, Mayla (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2024)
This study was conducted to test whether halal supply chain and product innovation affect the performance of MSMEs. The type of research used is quantitative data while the type of data is primary data. The population in this study were food and beverage MSME players in Pekanbaru city. The sampling technique used cluster sampling. The number of samples used in this study were 112 respondents. The data analysis used in this research is multiple linear regression analysis. From the results of the research conducted, it can be concluded that the halal supply chain has a significant effect on the performance of MSMEs. This shows that the better the implementation of the halal supply chain in MSME actors, the more MSME performance will be achieved. The product innovation variable has no effect on the performance of MSMEs. This shows that product innovation owned by MSME actors cannot support the achievement of MSME performance.